Air- and Dust-Borne Fungi in Indoor and Outdoor Home of Allergic Patients in a Dust-Storm-Affected Area. (18th August 2017) - Shabankarehfard, Elham; Ostovar, Afshin; Farrokhi, Shokrollah; Naeimi, Behrouz; Zaeri, Sasan; Nazmara, Shahrokh; Keshtkar, Mozhgan; Sadeghzadeh, Farzaneh; Dobaradaran, Sina
ABSTRACT: Despite the recent increases in fungi-induced allergic diseases, there is no report yet in the region of the Persian Gulf on concentration levels of fungi in relationship with health state. Therefore, our aim was to measure fungi prevalence as well as to evaluate the relationships between air- and dust-borne fungal genera and allergic diseases. A matched case-control study was carried out including 45 allergic cases and 45 age- and gender-matched controls for each individual. Indoor and outdoor dust and indoor air samples were collected from participant homes during May to October 2015. A Quick Take 30 Pump and sterile wet swab were used to determine fungal types and their amounts in the air (CFU/m 3 ) and dust (CFU/100 cm 2 ) samples, respectively. A significant reverse association was found between indoor dust-borne Alternaria and asthma (Odds ratio (OR) = 0.14, 95% CI = 0.02–0.86). Contrarily, increased levels of indoor air-borne Aspegillus fumigatus (OR = 2.00, 95% CI = 0.37–10.55) and Alternaria (OR = 3.00, 95% CI = 0.34–25.83) were correlated with asthma development. Also, correlation analysis showed a significant relation between indoor air-borne Penicillium levels and reactivity to skin prick test in asthmatic patients ( p = 0.04). Our findings support the notion that fungal exposures can either cause or prevent the development of allergic diseases. Accordingly, appropriate measures should be taken for a better management of fungi-induced allergic diseases.